2019
DOI: 10.1111/crj.13089
|View full text |Cite
|
Sign up to set email alerts
|

Endocan as a marker of disease severity in pulmonary thromboembolism

Abstract: Introduction The aim of this study is to determine the serum endocan levels in patients with pulmonary thromboembolism (PTE) and investigate whether a relationship exists between serum endocan levels and the disease severity. Materials and Methods The study included 85 patients with acute PTE and 40 healthy control subjects. The patients with PTE were divided into three groups at admission as “high‐risk”, “intermediate‐risk” and “low‐risk”, considering the guidelines of the European Society of Cardiology. Seru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 33 publications
0
14
0
Order By: Relevance
“…It has been demonstrated in many pathologies such as atherosclerosis, diabetic vasculopathy, vascular invasion in malignancies and new vascular formation, vascular thrombosis, acute coronary syndrome, and pulmonary embolism. [3][4][5][6] Serum endocan levels are increased in diseases with vascular involvement or invasion. 25,26 A study showed that there was a significant correlation between endocan messenger RNA (mRNA) levels and intratumoral microvessel density, mRNA of vascular endothelial growth factor, and vascular or venous invasion.…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated in many pathologies such as atherosclerosis, diabetic vasculopathy, vascular invasion in malignancies and new vascular formation, vascular thrombosis, acute coronary syndrome, and pulmonary embolism. [3][4][5][6] Serum endocan levels are increased in diseases with vascular involvement or invasion. 25,26 A study showed that there was a significant correlation between endocan messenger RNA (mRNA) levels and intratumoral microvessel density, mRNA of vascular endothelial growth factor, and vascular or venous invasion.…”
Section: Discussionmentioning
confidence: 99%
“…Two of those molecules are Endocan (Endothelial cell-Specific Molecule 1, ESM-1) and Lumican, but only few clinical studies address their applicability in NAFLD. The former is a proteoglycan well studied as an endothelial dysfunction biomarker in miscellaneous conditions like cancer, sepsis, pneumonia, pulmonary thromboembolism, chronic kidney disease, diabetes mellitus, preterm delivery-associated complications in neonates, and systemic sclerosis [6][7][8][9]. The latter is a small leucine-rich proteoglycan expressed in the extracellular matrix which regulates the process of collagen fibrillogenesis [10].…”
Section: Introductionmentioning
confidence: 99%
“…Destruction of glycocalyx results in the loss of heparan sulfate and exposure on the surface of endothelial cells of adhesion molecules inter-cellular adhesion molecule (ICAM-1) and vascular cell adhesion molecule (VCAM-1), which become accessible for circulating leukocytes involved in thrombosis [ 50 , 51 ]. One of the components of glycocalyx is the proteoglycan endocan [ 52 ]. Thus, expression of endocan is specific to the endothelium of the pulmonary and renal arteries [ 52 ].…”
Section: Potential Mechanisms For Primary Thrombosis In the Pamentioning
confidence: 99%
“…One of the components of glycocalyx is the proteoglycan endocan [ 52 ]. Thus, expression of endocan is specific to the endothelium of the pulmonary and renal arteries [ 52 ]. Increase in blood endocan levels in patients with CT angiographic evidence of a pulmonary thrombotic event is associated with a more severe course of the disease [ 52 ].…”
Section: Potential Mechanisms For Primary Thrombosis In the Pamentioning
confidence: 99%
See 1 more Smart Citation